Immunological responses and gut microbial shifts in Phthorimaea absoluta exposed to Metarhizium anisopliae isolates under different temperature regimes - Maingi, Felix Muendo; Akutse, Komivi Senyo; Ajene, Inusa Jacob; Omolo, Kevin Mbogo; Khamis, Fathiya Mbarak (Frontiers in Microbiology, 2023)
The invasive tomato leaf miner, Phthorimaea absoluta, is conventionally controlled through chemical insecticides. However, the rise of insecticide resistance has necessitated sustainable and eco-friendly alternatives. Entomopathogenic fungi (EPF) have shown potential due to their ability to overcome resistance and have minimal impact on non-target organisms. Despite this potential, the precise physiological mechanisms by which EPF acts on insect pests remain poorly understood. To attain a comprehensive understanding of the complex physiological processes that drive the successful control of P. absoluta adults through EPF, we investigated the impacts of different Metarhizium anisopliae isolates (ICIPE 665, ICIPE 20, ICIPE 18) on the pest's survival, cellular immune responses, and gut microbiota under varying temperatures. The study unveiled that ICIPE 18 caused the highest mortality rate among P. absoluta moths, while ICIPE 20 exhibited the highest significant reduction in total hemocyte counts after ten days at 25ºC. Moreover, both isolates elicited notable shifts in P. absoluta's gut microbiota. Our findings revealed that ICIPE 18 and ICIPE 20 compromised the pest's defence and physiological functions, demonstrating their potential as biocontrol agents against P. absoluta in tomato production systems.